Troposphere Sensing Using Grazing‐Angle GNSS‐R Measurement From LEO Satellites - Wang, Yang (Geophysical research letters, 2023)
This paper studies a new concept of using global navigation satellite system (GNSS) signals coherently reflected over relatively smooth ocean and ice surfaces from very low elevation angles (below ∼8°) and received by low Earth orbit (LEO) satellites to retrieve the tropospheric information. This approach can provide horizontal profiles of tropospheric zenith delay and total column water vapor (TCWV) with centimeter‐level high precision and spatial resolutions of tens of km by ∼1 km, depending on the elevation angle, with a sampling spacing of ∼100 m. This approach can potentially be applied to most sea ice and calm ocean areas and provide tropospheric sensing data, which can complement and augment existing observation systems. A few case studies are conducted in this paper using the Spire grazing‐angle GNSS‐R data. The retrieved TCWV is compared to ERA5 products and the Sentinel‐3 Ocean and Land Color Instrument measurements and shows promising performances. The errors associated with the GNSS‐R tropospheric measurements are also discussed. Plain Language Summary The atmospheric water vapor is an important component for the weather and climate systems and is difficult to measure, especially over ocean and ice surfaces. This paper studies a new approach to measuring atmospheric water vapor using global navigation satellite system (GNSS) signals reflected off ocean and ice surfaces. If the reflection is from a low elevation angle (below ∼8°) and the reflected signal is coherent (all signal rays are reflected in the same direction), this approach can provide very high precision observation of the horizontal gradients of the tropospheric delay and the vertically integrated atmospheric water vapor with good spatial resolutions. This paper presents the methodology of the proposed approach and a few case studies to demonstrate the feasibility and performance by comparing the GNSS‐R retrieved water vapor measurements with models and the Sentinel‐3 satellite radiometry measurements. The errors associated with the GNSS Reflectometry (GNSS‐R) tropospheric measurements are also discussed. Key Points A new tropospheric sensing concept is studied that relies on coherent‐reflection global navigation satellite system (GNSS) signals off ocean and ice surfaces Algorithms are developed and demonstrated using Spire grazing‐angle GNSS‐R data to retrieve tropospheric delay and water vapor The presented approach provides high‐precision tropospheric delay and total column water vapor horizontal profiles, as validated using the Sentinel‐3 Ocean and Land Color Instrument data